Particularidades de los motivos de consulta psicológica de los estudiantes que asisten a la Dirección de Bienestar Universitario, Universidad de Antioquia (2017)
ABSTRACT: We present the results of a research whose objective was to identify the particularities of the reasons for consultation of university students who came during the years 2012, 2013 and 2014 to the guidance-assistance process of the Department of Health Promotion and Disease Prevention of the Directorate of University Welfare of the University of Antioquia. The particularities refer to their definitions, categorization, form, content and changes evidenced in the way they are written by the team of psychologists, hence the reason for consultation has been understood as a translation exercise carried out by the professional of the concerns of the consultant.